(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article deals with the problems of Kazakh literature during the 2nd World War. Human values, existential questions of philosophy of life are told in literary works which were written on military theme. In this article actual problems of formation of military prose in the Kazakh literature will be considered. Emphasizing features of a military subject in the Kazakh literature and developing this thought, article faultlessly opens this actual problem, connecting it with destiny of the people of a military era. Differing in the vivacity, small genres of military years, deserved a special place in the history of domestic literature. Generally according to the contents they were propaganda character and had the special purposes. Such works had very important educational role in a unification of requirements of military times and desires of the people. Relying on thoughts of the brave and courageous batyr and at the same time writer, Bauyrzhan Momyshuly who established connection between literature and military destiny and I based military literature, problems of formation and development of military prose in the Kazakh literature are considered. Period when reached apogees its development of military-patriotic themes in Kazakh literature were the years of the Great Patriotic War.